Investigating the influence of volumetric hydrophobization on the formation of phase composition of cement stone and its physical-mechanical properties - Trofimova, Inna; Shpyrko, Nikolay (Eastern-European Journal of Enterprise Technologies, 2019)
We have examined the influence of the most widely used silicon-organic surface water repellent GKZH-11K on the physical-mechanical properties and the phase structure formation of cement is the fact that the introduction of the surface water repellent GKZH-11K to the composition of cement slurry leads to the formation of dispersive water-repellent films of various levels (size). These films adsorb at the surface of cement grains, as well as at the surface of hydrated components of cement particles, Са(ОН)2, calcium sulphoaluminates. It was determined that the disperse hydrophobic films partially block the penetration of water into the surface of cement grains and alter the kinetics of hydration. This leads to a decrease in the degree of hydration and the content of Са(ОН)2 in cement stone, resulting in the reduced shrinkage at hardening. At the same time, the disperse films adsorbed on neighboring hydrated cement particles within the contacts occurred in the process of their condensation can form hydrogen and chemical relationships. This interaction between the particles’ films, despite the reduction in the degree of hydration, leads to a decrease in water absorption, improving the strength of cement stone, which in this case is also determined by the number and area of contacts per unit volume of cement stone. The overlap of pores with hydrophobic chains decreases the permeability of cement stone throughout its entire volume, which contributes to the growth of operational reliability and durability of structures, particularly thin-walled. Using this admixture for volumetric hydrophobization could greatly prolong repair-free operation of thin-walled products and structures, as well as bring down cost as there is no need to apply materials to protect the surface of concrete.